An inhibitor of apoptosis (SfIAP) interacts with SQUAMOSA promoter‐binding protein (SBP) transcription factors that exhibit pro‐cell death characteristics. (10th August 2018) - Kessens, Ryan; Sorensen, Nick; Kabbage, Mehdi
Abstract: Despite the importance of proper cell death regulation across broad evolutionary distances, an understanding of the molecular machinery underpinning this fundamental process in plants remains largely elusive. This is despite its critical importance to development, homeostasis, and proper responses to stress. The identification of endogenous plant regulators of cell death has been hindered by the fact that many core regulators of cell death in animals are absent in plant genomes. Remarkably, numerous studies have shown that the ectopic expression of animal prosurvival genes in plants can suppress cell death imposed by many stresses. In this study, we capitalize on the ectopic expression of one of these animal prosurvival genes, an inhibitor of apoptosis from Spodoptera frugiperda ( SfIAP ), to identify novel cell death regulators in plants. A yeast two‐hybrid assay was conducted using SfIAP as bait to screen a tomato cDNA library. This screen identified several transcription factors of the SQUAMOSA promoter‐binding protein (SBP) family as potential SfIAP binding partners. We confirmed this interaction in vivo for our top two interactors, SlySBP8b and SlySBP12a, using coimmunoprecipitation. Interestingly, overexpression of SlySBP8b and SlySBP12a induced cell death in Nicotiana benthamiana leaves. Overexpression of these two transcription factors also induced the accumulation of reactive oxygen species and enhanced the growth of the necrotrophic pathogen Alternaria alternata . Fluorescence microscopy confirmed the nuclear localization of both SlySBP8b and SlySBP12a, while SlySBP12a was also localized to the ER membrane. These results suggest a prodeath role for SlySBP8b and SlySBP12a and implicate ER membrane tethering as a means of regulating SlySBP12a activity.